Reacting in time to qualification needs : towards a cooperative implementation? : proceedings of a conference organised by the WZB on the 27-28 September 2001, within the research network FreQuenz supported by the Federal ministry for training and research (BMBF) - Rouault, Sophie [Herausgeber]; Oschmiansky, Heidi [Herausgeber]; Schömann, Isabelle [Herausgeber] (My University, 2002)
Die Erhöhung des Qualifikationsniveaus der Arbeitskräfte ist ein zentrales Anliegen der Regierungen der Europäischen Union: im globalen ökonomischen Wettbewerb spielt die Entwicklung des Humankapitals eine zentrale Rolle. Diesem Ausgangspunkt entsprechend untersuchen die Beiträge des Bandes, wie der identifizierte Qualifizierungsbedarf von Unternehmen und Beschäftigten gedeckt werden kann. Der gemeinsame Fokus besteht in der Analyse von Koordinierungsmustern der Akteure der nationalen, regionalen und supranationalen Ebene für die Implementation und Institutionalisierung neuer Arbeitsmarktarrangements, um ein effektiveres Qualifizierungs-Matching zu gewährleisten. Die Beiträge basieren auf Vorträgen für einen internationalen Workshops des Wissenschaftszentrums Berlin am 27. und 28. September 2001. Inhalt: Sophie Rouault: Qualification need and multi-level coordination: Introducing a research question; Heidi Oschminasky, Sophie Rouault, Isabelle Schömann: Three research fields and a summary of results; - Part I: The role of networks in the implementation process of jobrotation (Heidi Oschmiansky: Implementing jobrotation in Germany: labour market actors' contribution to meet skill needs; John Houman Sorensen: Job-rotation schemes in Denmark : An active labour market policy instrument and its dependence on qualification strategies and economic situation of firms; Jouko Nätti: Job Rotation in Finland: National and local experiments; Lizzi Feiler: Co-operative approaches to identify and meet qualification needs. The implementation systems of Jobrotation and programmes in Austria); - Part II: Answering territorial qualification needs through new corporate and employment forms (Sophie Rouault: Answering qualification needs through multiple jobholding arrangements: multi-level coordination in France and Sweden; Ton Wilthagen, Harm van Lieshout, Martijn van Velzen: Employment and training pools in the Netherlands: analytical remarks and examples; Bengt Lorendahl: Neo-cooperatives to support self- employment? The Swedish Case; Claudia Weinkopf: Service pools as qualifying alternative in services to private households); - Part III: The role of social partners in the implementation of skill needs (Isabelle Schömann: A right to vocational training: The anticipative action of workers' representatives in selected European countries; Ralf Rogowski, Isabelle Schömann: The role and impact of social partners on training in the European Union; Philippe Mehaut: What is the future of vocational education? Chronicle of unsuccessful negotiations; Harm van Lieshout, Ton Wilthagen: Transitional labour markets in action: new developments in the Dutch vocational education and training market). (IAB2)
Frühzeitige Reaktion auf Qualifikationsbedarfe : auf dem Weg zu einer kooperativen Implementierung?
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 3.2 Unternehmen und Behörden; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 1.2.2.3 Beschäftigungsformen; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; G 2.3.4 Qualifikationswandel; S 3.5.4 Sozialpartner; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; I 2.2 Europa; Beschäftigungsform; Qualifikationsbedarf; Unternehmen; Arbeitnehmer; Jobrotation; Internationaler Vergleich; Arbeitszeitmodell; Berufliche Weiterbildung; Sozialpartner; Interkulturelle Faktoren; Netzwerk; Arbeitsmarktpolitik; Dänemark; Finnland; Österreich; Frankreich; Schweden; Niederlande; Europäische Union